THE CONCEPT OF A MATHEMATICS LITERACY LEARNING MODEL BASED ON LOCAL WISDOM IN INCLUSIVE HIGH SCHOOLS IN DENPASAR CITY - Sukendra, I Komang; Putu Dessy Fridayanthi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Inclusive schools with an educational service system require that children with special needs be educated alongside their peers according to their abilities. Until now, a model for mathematics literacy learning based on local wisdom in inclusive high schools has not been available. This study aims to: (1) Analyze local wisdom in inclusive high schools, (2) Analyze the model of mathematics literacy learning based on local wisdom in inclusive high schools, and (3) Construct the concept of a mathematics literacy learning model based on local wisdom in inclusive high schools. This study uses both quantitative and qualitative approaches. The quantitative results illustrate the analysis of the influence of local wisdom-based learning (X) on learning independence (Y1) and student creativity (Y2), as well as the role of teachers in developing mathematics literacy learning models in inclusive high schools in Denpasar City. The qualitative approach is conducted to complement the data collected using the quantitative approach. The qualitative analysis results can be summarized as follows: (1) The model for mathematics literacy learning based on local wisdom in inclusive high schools needs improvement. (2) The implemented model of mathematics literacy learning based on local wisdom in inclusive high schools are highly varied, and (3) It is urgent and necessary to formulate a new concept for a mathematics literacy learning model based on local wisdom for students in inclusive education schools. The development of this new concept needs to involve various parties, including policymakers, community leaders, and program implementers such as school principals, teachers, and parents.